2022
DOI: 10.1542/peds.2021-051822
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Pediatric Universal Behavioral Health Care at Federally Qualified Health Centers

Abstract: BACKGROUND: Research supports integrated pediatric behavioral health (BH), but evidence gaps remain in ensuring equitable care for children of all ages. In response, an interdisciplinary team codeveloped a stepped care model that expands BH services at 3 federally qualified health centers (FQHCs). METHODS: FQHCs reported monthly electronic medical record data regarding detection of BH issues, receipt of services, and psychotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…This study contributes to a dearth of literature on integrated pediatric care models in FQHCs (Burkhart et al, 2020; Sheldrick et al, 2022). This intervention relied on strong buy-in from FQHC leadership, as well as resources to hire social workers, purchase electronic tablets, pay for screening costs, and support the dedicated time of quality improvement personnel to oversee implementation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study contributes to a dearth of literature on integrated pediatric care models in FQHCs (Burkhart et al, 2020; Sheldrick et al, 2022). This intervention relied on strong buy-in from FQHC leadership, as well as resources to hire social workers, purchase electronic tablets, pay for screening costs, and support the dedicated time of quality improvement personnel to oversee implementation.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, our results suggest that disseminating the multicomponent screening intervention may support populationlevel improvement in the early detection and management of pediatric developmental delays and behavioral health issues. This study contributes to a dearth of literature on integrated pediatric care models in FQHCs (Burkhart et al, 2020;Sheldrick et al, 2022). This intervention relied on strong buy-in from FQHC leadership, as well as resources to hire social workers, purchase electronic tablets, pay for screening costs, and support the dedicated time of quality improvement personnel to oversee implementation.…”
Section: Screening Process Stepsmentioning
confidence: 99%
“…Psychologists can collaborate with care coordinators to support families as they navigate siloed systems that are uniquely challenging for prohibited populations. Substantial evidence demonstrates the effectiveness of care coordination for chronic medical illness and there is emerging evidence to support its effectiveness in addressing behavioral health concerns (Godoy et al, 2019), including within integrated models (e.g., Sheldrick et al, 2022).…”
Section: Clinicianmentioning
confidence: 99%
“…Starting in mid-2016, 3 Massachusetts-based federally qualified health centers (FQHCs) began implementing Transforming and Expanding Access to Mental Health in Urban Pediatrics (TEAM UP), which is a comprehensive integrated MH care model that serves children from birth through young adulthood . As further described in a recent study of TEAM UP, TEAM UP focuses on promotion, prevention, and early identification of emerging MH issues, swift access to MH services, and psychiatric consultation for complex cases. Services are delivered by a team of MH clinicians, community health workers, and primary care clinicians, who implement the model within a learning community that includes technical assistance, clinical training, and an evaluation group to prove and improve the model.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using electronic medical records at TEAM UP FQHCs documented high rates of screening, effective use of warm hand-offs (ie, in-person transfer of care between 2 clinicians) to connect children to care, reductions in polypharmacy, and increases in diagnosis and treatment for attention-deficit/hyperactivity disorder, although the data were limited to TEAM UP electronic medical records, and, thus, no comparison groups were available. An additional study using claims data, which included the same 6 comparison sites, indicated that after 1.5 years of implementation, TEAM UP was associated with increases in all-cause primary care visits, especially among children with baseline MH conditions, with no changes in avoidable utilization.…”
Section: Introductionmentioning
confidence: 99%